Fast Ca2+ Transients of Inner Hair Cells Arise Coupled and Uncoupled to Ca2+ Waves of Inner Supporting Cells in the Developing Mouse Cochlea - Eckrich, Tobias; Blum, Kerstin; Milenkovic, Ivan; Engel, Jutta (Frontiers in Molecular Neuroscience, 2018)
Before the onset of hearing, which occurs around postnatal day 12 (P12) in mice, inner hair cells (IHC) of the immature cochlea generate sound-independent Ca2+ action potentials (AP), which stimulate the auditory pathway and guide maturation of neuronal circuits. During these early postnatal days, intercellular propagating Ca2+ waves elicited by ATP-induced ATP release are found in inner supporting cells (ISC). It is debated whether IHCs are able to fire Ca2+ APs independently or require a trigger by an ISC Ca2+ wave. To identify the Ca2+ transients of IHCs underlying Ca2+ APs and to analyze their dependence on ISC Ca2+ waves, we performed fast Ca2+ imaging of Fluo-8 AM-loaded organs of Corti at P4/P5. Fast Ca2+ transients (fCaTs) generated by IHCs were simultaneously imaged with Ca2+ waves in ISCs. ISC Ca2+ waves frequently evoked bursts consisting of >5 fCaTs in multiple adjacent IHCs. Although Ca2+ elevations of small amplitude appeared to be triggered by ISC Ca2+ waves in IHCs of Cav1.3 knockout mice we never observed fCaTs, indicating their requirement for Ca2+ influx through Cav1.3 channels. The Ca2+ wave-triggered Ca2+ upstroke in wildtype IHCs occurred 0.52 ± 0.27 s later than the rise of the Ca2+ signal in the adjacent ISCs. In comparison, superfusion of 1 µM ATP elicited bursts of fCaTs in IHCs starting 0.99 ± 0.34 s prior to Ca2+ elevations in adjacent ISCs. PPADS irreversibly abolished Ca2+ waves in ISCs and reversibly reduced fCaTs in IHCs indicating differential involvement of P2 receptors. IHC and ISC Ca2+ signals were however unaltered in P2X2R/P2X3R double knockout or in P2X7R knockout mice. Together, our data revealed a fairly similar occurrence of fCaTs within a burst (56.5 %) compared with 43.5 % as isolated single fCaTs or in groups of 2 - 5 fCaTs (minibursts). We provide evidence that IHCs autonomously generate single fCaTs and minibursts whereas bursts synchronized between neighboring IHCs were mostly triggered by ISC Ca2+ waves. Neonatal IHCs thus spontaneously generate electrical and Ca2+ activity, which is enhanced and largely synchronized by activity of ISCs of Kölliker’s organ indicating two sources of spontaneous activity in the developing auditory system.